Reliability of Wound Measurement Methods - Dahlia Musa; Frank Guido-Sanz; Mindi Anderson; Salam Daher (IEEE Open Journal of Instrumentation and Measurement, 2022)
Reliable and accurate measurement methods are necessary for the clinical assessment of wounds. Repeated measure of a wound indicates whether its healing is progressing or deteriorating, and if alternate treatment must be initiated. Many wound measurement techniques lack accuracy and reliability. Technology: We developed a software prototype that calculates 3-D wound measurements from 3-D scans. We conducted a study to compare the software prototype to physical and 2-D image measurement techniques commonly used by clinicians. We compared inter-rater reliability between the techniques and measurements (i.e., length, width, depth, perimeter, and surface area). Results: Inter-rater reliability was good or excellent for the physical, image, and software measurement techniques; however, there were significant differences in measurements between the techniques. For complex measurements (i.e., perimeter and surface area), the reliability of the software exceeded that of the physical and image techniques. Conclusion: Although inter-rater reliability was high for all measurement techniques, there was significant variability between the techniques. The software was overall most reliable, especially for calculation of complex measurements. Clinical Impact: Reducing the variability of wound measurements may improve patient outcomes, reduce wound prevalence, and mitigate the associated morbidity, mortality, and costs of these occurrences.